Analisis Struktural dan Nilai Moral dalam Cerpen “Rembulan Di Mata Ibu” Karya Asma Nadia - Hesti Indah Sari; Monalisa Ratuliu (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article aims to analyze the structural and moral values in the short story Rembulan in the Eyes of Mother by Asma Nadia. Short stories are a form of fiction that usually focus on one event, have a single plot, and have a relatively short and limited time scope. The type of research used is structural study. This study focuses on the coherence between the intrinsic elements of short stories. Theme, setting, plot, point of view and characters must have a reciprocal relationship, determine and influence each other so that they form a complete short story and the researcher will research and explain the moral values that the short story writer wants to convey to the reader.